2011
DOI: 10.1007/s10646-011-0787-x
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific responsiveness of four enzymes to endosulfan and predation risk questions their usefulness as general biomarkers

Abstract: General biochemical biomarkers are widely used in current ecotoxicology and may function as early warning signals. We have, however, poor knowledge on how ecologically similar species differ in their biomarker responsiveness and how predation risk may affect these biomarkers, potentially in an interactive way with pesticides. We evaluated this by exposing four corixid water bug species to combinations of endosulfan and predation risk and quantifying the activity of four general enzymatic biomarkers: acetylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 77 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…We measured the activity of AChE on the heads using a for insects modified version of the protocol of Ellman (Jensen et al 1997). This enzyme has an important function in the nervous system by catalysing the breakdown of acetylcholine and higher activity levels have been shown to be positively related to escape swimming speed (Trekels et al 2012;Bonansea et al 2016). We homogenized the heads in 250 µl PBS and after centrifugation we used the supernatant for the analysis.…”
Section: Response Variablesmentioning
confidence: 99%
“…We measured the activity of AChE on the heads using a for insects modified version of the protocol of Ellman (Jensen et al 1997). This enzyme has an important function in the nervous system by catalysing the breakdown of acetylcholine and higher activity levels have been shown to be positively related to escape swimming speed (Trekels et al 2012;Bonansea et al 2016). We homogenized the heads in 250 µl PBS and after centrifugation we used the supernatant for the analysis.…”
Section: Response Variablesmentioning
confidence: 99%
“…PO activity can increase, decrease or remain constant) depending on the studied freshwater invertebrate and the tested contaminants (e.g. Campero et al, 2008;Lilley et al, 2012;Trekels et al, 2012;Janssens and Stoks, 2013a). Lilley et al (2012) documented an increase in PO activity (humoral immunity) in Chironomus riparius midge larvae exposed to tributyltin and explained this as a compensatory response for the reduced cellular immunity.…”
Section: Pesticide Effectsmentioning
confidence: 99%
“…Several studies demonstrated synergistic effects between pesticide exposure and predator cues for life history traits such as mortality and growth rate (e.g., Releya and Mills, 2001;Campero et al, 2007;Trekels et al, 2011). Yet, such synergistic effects on life history are not always detected (e.g., Coors and De Meester, 2008;Jansen et al, 2011) and physiological traits have been largely ignored (but see Campero et al, 2007;Trekels et al, 2012). Three types of neglected physiological traits are especially relevant to consider in the context of synergistic interactions between exposure to pesticides and predator cues as these types are related to fitness and are known to be influenced by both stressors separately.…”
Section: Introductionmentioning
confidence: 99%